Phytochemical Screening and Antibacterial Activity of Bryophytes - Kadam Pratima S (International Journal of Life Sciences, 2017)
In this paper we study antibacterial activity and phytochemical screening of the bryophytes. The bryophytes possess some bioactive compounds and therefore are medicinally very useful plants. They contain pools of secondary metabolites, which are unique .The antimicrobial activity was assessed using agar well diffusion method against the two bacterial strains from the bryophytes viz Anthoceros erectus, Asterella angusta, Cyathodium tuberosum, Plagiochasma articulata and Targionia hyphophylla the studies of phytochemical constituents revealed presence of alkaloids, flavonoids, coumarins, phenols, tannins, steroids, and sugars. The antimicrobial activity is due to the presence of secondary metabolites. It was highest in Targionia hyphophylla and least in Cyathodium tuberosum. The above observations suggest that due to significant antibacterial activity of the bryophytes they have good potential in drug development.